2018
DOI: 10.1111/ppc.12307
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with sleep in family caregivers of individuals with dementia

Abstract: Our study suggests that sleep quality for family caregivers of individuals with dementia varies considerably from night to night. Understanding the complex interrelationships among caregivers' sleep and other contributing variables is an important first step toward the development of individualized and effective treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 54 publications
(113 reference statements)
6
40
0
4
Order By: Relevance
“…All previous international studies identified an average PSQI >/ 5 in dementia caregiver studies [15] highlighting the prevalence of the issue. As expected, and consistent with previous studies [13], Australian caregivers of PLWD have a high prevalence of poor sleep with 94% of participants classified as poor sleepers. The PSQI global score (9.12 ± 3.7) was higher than those found in some dementia caregiver studies [24,25] but comparable with others [13].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…All previous international studies identified an average PSQI >/ 5 in dementia caregiver studies [15] highlighting the prevalence of the issue. As expected, and consistent with previous studies [13], Australian caregivers of PLWD have a high prevalence of poor sleep with 94% of participants classified as poor sleepers. The PSQI global score (9.12 ± 3.7) was higher than those found in some dementia caregiver studies [24,25] but comparable with others [13].…”
Section: Discussionsupporting
confidence: 92%
“…As expected, and consistent with previous studies [13], Australian caregivers of PLWD have a high prevalence of poor sleep with 94% of participants classified as poor sleepers. The PSQI global score (9.12 ± 3.7) was higher than those found in some dementia caregiver studies [24,25] but comparable with others [13]. The PSQI sub-components which greatest contributed to the overall score were sleep latency (time taken to fall asleep), sleep quality (overall subjective quality) and sleep disturbances.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is important to deliver cost effective care which improves outcomes for people with dementia in clinical practice, 37 and is being used in recently published studies measuring sleep in people with dementia including a randomised controlled trial, 30,[38][39][40][41] these results will also be helpful for researchers to use in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disturbances increase the risk of obesity, diabetes, and cardiovascular diseases [6][7][8][9]. Features of sleep disorders among these caregivers include shortened sleep time, decreased sleep efficiency, wake after sleep onset (WASO), and less slow-wave sleep [10][11][12][13]. Nocturnal awakening is associated with the activation of sympathetic nerve activity [9].…”
Section: Introductionmentioning
confidence: 99%